2017
DOI: 10.1002/2017jb014218
|View full text |Cite
|
Sign up to set email alerts
|

On the kinematics and dynamics of crystal‐rich systems

Abstract: Partially molten rocks, often called a mush, are examples of a hydrogranular mixture where the dynamics are controlled by both fluid and crystal‐crystal interactions. An obstacle to progress in understanding high‐temperature hydrogranular systems has been the lack of adequate levels of description of microphysical processes. Here we rationalize the hydrogranular kinematic and dynamic states by applying the concept of particle (crystal) force chains. We exemplify this with discrete‐element computational fluid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(130 citation statements)
references
References 257 publications
(334 reference statements)
4
115
0
Order By: Relevance
“…Our simulations are consistent with the discrepancies in experimental measurements constraining the onset of shear thinning behavior with different apparatuses (Bergantz et al, ; Mader et al, ). For example, our comparison of the Couette device and the rotational viscometer is consistent with the measurements from Ishibashi () and Mueller et al ().…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our simulations are consistent with the discrepancies in experimental measurements constraining the onset of shear thinning behavior with different apparatuses (Bergantz et al, ; Mader et al, ). For example, our comparison of the Couette device and the rotational viscometer is consistent with the measurements from Ishibashi () and Mueller et al ().…”
Section: Discussionsupporting
confidence: 91%
“…Summarizing, our analyses show that the observed diversity of rheological behavior in different laboratory geometries is related to varying microphysical properties of the crystalline phase, as hypothesized by Bergantz et al (). In contrast to Bergantz et al (), however, the different microphysical properties in our simulations are not related to a varying nature of the contact between crystals, which Bergantz et al () categorized as either frictional or lubricated. In fact, the crystals in our simulations never touch, because the pressure in the thin melt film separating the crystal interfaces impedes direct contact, at least for the smooth crystal interface considered in our simulations.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This could explain rhythmic layering but also larger-scale zonation observed in large igneous bodies. Bergantz et al (2017) used a discrete-element computational fluid dynamics simulation to study the intrusion of basalt into an olivine-basalt mush by considering crystalscale force chains, crystal transport, and mixing processes. They found that the conditions for mechanical "lock up" were not uniquely identified by a specific crystal volume fraction.…”
Section: Magma Chamber To Plutonmentioning
confidence: 99%